Sport, Innovation and Strategic Management: A Systematic Literature Review - Anne Tjonndal (BBR: Brazilian Business Review)
Sport organizations adapt, renew and develop through creative and novel ideas. The various strategies for innovation applied by sport organizations hold the potential to radically change how we play, view and organize sport. In other words, through strategy, strategic management and innovation modern sport is shaped and improved. To date, limited scholarly attention has been given to strategy, strategic management and innovation in sport. However as the present review will demonstrate, sport innovation and strategic management of sports innovations are crucial for improvement of athletic performance. Furthermore, current research indicates that sport innovation can be a valuable tool to combat demanding challenges in modern sport, such as social exclusion. Therefore, innovation and strategic management needs specific attention within the sport sciences. The present paper attempts to provide more insight in the current body of research on sport innovation and strategic management. Finally, some recommendations for further research in this field is formulated.